2019
DOI: 10.1021/acscatal.9b02313
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Vicinal Dichlorination of Unactivated Alkenes

Abstract: Organocatalytic strategies for the programmed, catalytic oxidation of π-bonds through regioselective halogenation remain comparatively underdeveloped. The vicinal dichlorination of unactivated alkenes is a pertinent example, where stoichiometric reagents and prefunctionalization steps are often employed. This is surprising given the prominence of the 1,2-dichloro moiety in an array of bioactive natural products of both terrestrial and marine origin. Inspired by Willgerodt’s seminal discovery in 1886 that PhICl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 83 publications
1
29
0
2
Order By: Relevance
“…[18] Contemporaneous reports by this laboratory [19] and the Jacobsen laboratory [20] have demonstrated that simple aryl iodide/ HF combinations efficiently support the difluorination of alkenes in the presence of astoichiometric oxidant. Enabled by the in situ generation of hypervalent ArI III F 2 intermediates, [21] these transformations have also been translated to an enantioselective paradigm [22,23] using C 2 -symmetric Ishihara-MuÇiz scaffolds. [24] Encouraged by the effectiveness of this platform the fluorocyclization of simple 1-(allyloxy)-4bromobenzene (5)was explored as described in Table 1.…”
mentioning
confidence: 99%
“…[18] Contemporaneous reports by this laboratory [19] and the Jacobsen laboratory [20] have demonstrated that simple aryl iodide/ HF combinations efficiently support the difluorination of alkenes in the presence of astoichiometric oxidant. Enabled by the in situ generation of hypervalent ArI III F 2 intermediates, [21] these transformations have also been translated to an enantioselective paradigm [22,23] using C 2 -symmetric Ishihara-MuÇiz scaffolds. [24] Encouraged by the effectiveness of this platform the fluorocyclization of simple 1-(allyloxy)-4bromobenzene (5)was explored as described in Table 1.…”
mentioning
confidence: 99%
“…Consequently, a series of alternatives have been developed based on the ionic dichlorination reactions of alkenes [4] . These include the Willgerodt reagent (PhICl 2 ), [4c] SO 2 Cl 2 , [4d] the Mioskowski reagent (Et 4 NCl 3 ), [4w] NCS‐PPh 3 (the Yoshimitsu reagent), [4n] and combinations of chloride salts and oxidants, [4l,m,o,x,z] among others (Scheme 1 a). These electrophilic addition reactions typically exhibit anti selectivity as a result of the formation of a chloriranium ion as the reaction intermediate.…”
Section: Methodsmentioning
confidence: 99%
“…该方法为合成具有 生物等排体的富氟结构提供了一定的参考价值. 次年, 该课题组 [63] 又利用碱金属氯化铯与 Selectfluor 原位生成 p-TollCl 2 , 并在其作用下实现了烯烃的邻位二氯化(Eq. 28).…”
Section: 卤化反应unclassified